If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 51 + 15x = 3 Reorder the terms: 51 + -3x + 15x = 3 Combine like terms: -3x + 15x = 12x 51 + 12x = 3 Solving 51 + 12x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-51' to each side of the equation. 51 + -51 + 12x = 3 + -51 Combine like terms: 51 + -51 = 0 0 + 12x = 3 + -51 12x = 3 + -51 Combine like terms: 3 + -51 = -48 12x = -48 Divide each side by '12'. x = -4 Simplifying x = -4
| 14+r=26 | | X=17+4 | | x^2+10x+18=x | | 4(3n-1.2)-0.5=9.5+0.2 | | x+77=394 | | X=29-9 | | 25x-20=15x+15 | | 4d+13-6-13.20= | | 45=3s | | 2x+3y=1700 | | 25=17+m | | X=28+22 | | 3d+13-6-13.20=1.55 | | X=21+11 | | 3d+13-6-13.20=1.60 | | 128+x+40+82=360 | | x+5.25=7.55 | | X=19+11 | | 3d+13-6-13.20=2.07 | | X=28+14 | | 6=1.2 | | s-3.2=6 | | X=19+13 | | X=25+17 | | 12.3=14-b | | t+13=3 | | 8t^2+17t-25=0 | | X=18-11 | | f(x)=4x^2+8x+11 | | 7.09=3+y | | -6n+48=6u | | 1+12= |